Antibiotic Use among Vietnamese Children Hospitalized with Pneumonia - Xuan, Bui Thi; Van Dem, Pham; Thanh Nam, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
Background: The use of antibiotics in the treatment of community-acquired pneumonia in children from 2 months to 5 years old at a tertiary hospital in Vietnam still has many shortcomings. Materials & Methods: A cross-sectional descriptive study was carried out based on retrospective data and information collected from 154 inpatient medical records for community-acquired pneumonia at the Department of Pediatrics - Bach Mai Hospital, Hanoi, Vietnam, in 2021. Clinical and laboratory information, information on antibiotic use in community-acquired pneumonia in pediatric patients, and information on the appropriateness of antibiotic use were collected and analyzed. Results: There were 12 antibiotic regimens initially selected to be used to treat community-acquired pneumonia at the hospital, of which four regimens used one antibiotic and eight regimens used combined antibiotics. The rate of combination regimen gradually increased with disease severity, which was 22.3%, 38.5%, and 50% for mild pneumonia, severe pneumonia, and very severe pneumonia, respectively. The most commonly used antibiotic groups in the initial regimen are penicillin/β-lactamase inhibitor (alone regimen) and penicillin/β-lactamase inhibitor in combination with macrolides (combination regimen). The rate of initial treatment regimens that were not suitable according to the recommendations accounted for 99.4%. There were 83/154 cases where patients were prescribed antibiotics inappropriately in terms of dose and rhythm or both. Conclusion: The use of antibiotics in the treatment of community-acquired pneumonia in children at a tertiary hospital still has shortcomings. It is necessary to develop a system of assessment and monitoring of antibiotic use, from which timely adjustments and controls can be made, to limit the ability of bacteria to develop drug resistance.